Quantification of endogenous Angiotensin 1-10, 1-9, 1-8, 1-7, and 1-5 in human plasma using micro-UHPLC-MS/MS: Outlining the importance of the pre-analytics for reliable results - Maurer, Jonathan; de Groot, Anke; Martin, Léon; Grouzmann, Eric; Wuerzner, Grégoire; Eugster, Philippe J. (Journal of pharmaceutical and biomedical analysis, 2024)
Angiotensin peptides (ANGs) play a central role in the renin–angiotensin–aldosterone system, rendering them interesting biomarkers associated with hypertension. Precise quantification of circulating ANGs holds the potential to assess the activity of angiotensin-converting enzyme (ACE), a key protease targeted by widely prescribed drugs, namely ACE inhibitors. This ability could pave the way for personalised medicine, offering insights into the prescription of inhibitors targeting either the proteases or the receptors within the system. Despite recent developments in liquid chromatography–mass spectrometry (LC-MS) methods for measuring circulating ANG concentrations, comprehensive stability studies of ANGs in human plasma are absent in the literature, raising concerns about the reliability of measured concentrations and their link to clinical conditions. To address this critical gap, we conducted an exhaustive evaluation of the pre-analytical stability of ANG1–10, ANG1–9, ANG1–8, ANG1–7, and ANG1–5. By employing surfactants to mitigate non-specific adsorption and a dedicated mix of protease inhibitors to limit protease activity, we established an MS-based assay for these five peptides. We used this method to quantify circulating concentrations of ANGs in the plasma of 11 healthy donors and 3 patients under kidney dialysis. Our findings revealed that ANG1–10 and ANG1–8 circulate at concentrations ranging from 1 to 10 pM in healthy subjects and exhibit a high degree of correlation. Notably, ANG1–9, ANG1–7, and ANG1–5 were undetectable in any of the 14 patients, despite a sub-picomolar limit of detection. This strikingly contrasts with the reference concentrations reported in the literature, which typically fall within the picomolar range. In light of these discrepancies, we strongly advocate for rigorous pre-analytical considerations and comprehensive stability studies to ensure reliable results. We emphasise the pivotal role of heightened pre-analytical awareness within the clinical chemistry community, and we hope for continued growth in this critical area. •A comprehensive stability study of angiotensin peptides (ANGs) is provided.•This method allows the detection of sub-picomolar ANGs concentrations.•ANGs are very sensitive to protease activity, resulting in fast metabolism.•We measured ANGs concentrations lower than previously reported in literature.